A ratio decidendi dos precedentes judiciais : uma análise sobre a insuficiência das técnicas de identificação no constitucionalismo contemporâneo - Benevides, Nauani Schades (2019)
The Brazilian legal system has been gradually giving greater importance to judicial precedents. Notwithstanding this fact, there were no major theoretical concerns regarding the way of dealing with precedents, and its use is ruled, albeit unconsciously, by the theoretical common sense historically established in the country: the normativist paradigm typical of legislative law. In fact, the theoretical development regarding specifically this subject in Brazil, mainly as a result of the advent of the Code of Civil Procedure of 2015, is mostly based on concepts that are characteristic of a legislative law or is based on the simple importation of the Anglo-Saxon tradition`s institutes. It is in this context that the national doctrine defends the importation of the concept of ratio decidendi as adequate to the use of the brazilian model of precedent, which would be sufficient to overcome the failed idea of precedent as a general and abstract statement like the brazilian súmula. In this sense, the present research aims to analyze the applicability of techniques for the determination of the precedent’s ratio decidendi. For this, it examines the historic of valorization of judicial precedents in Brazilian law, the national doctrinal thoughts on the subject and how they understand it and the theories of the main exponents on ratio decidendi of common law. Once this exposition has been made, adopting the theoretical framework of Philosophical Hermeneutics conceiving Law as integrity in a systemic paradigm, each of theories and their respective techniques, is analyzed critically, evaluating its compatibility with contemporary constitutionalism. Given the insufficiency of techniques for determining the binding element of the judicial precedent, it is proposed to use the precedent from its hermeneutic force, which varies according to formal and material elements. The research was developed through a qualitative approach, through the use of historical, hermeneutical, argumentative and dogmatic methods, and is bound to the research line "Justice, means of defense and challenging judicial decisions" of the Master Program in Procedural Law of the Universidade Federal do Espírito Santo.